Charlie D : the story of the legendary bond trader - Falloon, William D. (New York : J. Wiley & Sons, 1997)
This book is an autobiography of Charlie D - a legendary bond trader.
osa15/05/13
Loans
Keywords: DiFrancesca, Charles; Chicago Board of Trade; Floor traders (Finance) -- United States -- Biography; Bond traders